2020
DOI: 10.18632/aging.102780
|View full text |Cite
|
Sign up to set email alerts
|

Immune-related key gene CLDN10 correlates with lymph node metastasis but predicts favorable prognosis in papillary thyroid carcinoma

Abstract: The functions of immune cells in lymph node metastasis (LNM) have attracted considerable attention. This study aimed to screen the key immune-related and LNM-related genes in PTC. In the discovery phase, the immune-related genes in LNM were screened by using bioinformatics methods. In the validation phases, the association of the genes with LNM was first confirmed in a cohort from The Cancer Genome Atlas and a cohort based on a tissue chip. Then, the relationship of the genes with immune cell infiltration was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 31 publications
(31 reference statements)
3
19
0
2
Order By: Relevance
“…A previous study has con rmed that CLDN10 was an immune-related gene and could predict the prognosis of papillary thyroid carcinoma [16]. In our analysis, the decreased expression of CLDN10 was associated with increased in ltration of several major immune cells, potentially enhancing the body's anti-tumor immune response, which partly explains why low expression of CLDN10 was associated with better prognosis in gastric cancer.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…A previous study has con rmed that CLDN10 was an immune-related gene and could predict the prognosis of papillary thyroid carcinoma [16]. In our analysis, the decreased expression of CLDN10 was associated with increased in ltration of several major immune cells, potentially enhancing the body's anti-tumor immune response, which partly explains why low expression of CLDN10 was associated with better prognosis in gastric cancer.…”
Section: Discussionsupporting
confidence: 61%
“…Previous reports have shown that CLDN10 is highly expressed in hepatocellular carcinoma, papillary thyroid carcinoma and lung adenocarcinoma. Its expression is associated with poor prognosis of hepatocellular carcinoma, but with better survival of thyroid papillary carcinoma and lung adenocarcinoma [15][16][17]. In addition, down-regulated CLDN10 is correlated with poor prognosis of ovarian cancer and clear cell renal cell carcinoma [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have shown that CLDN10 is highly expressed in hepatocellular carcinoma, papillary thyroid carcinoma and lung adenocarcinoma. Its expression is associated with poor prognosis of hepatocellular carcinoma, but with better survival of thyroid papillary carcinoma and lung adenocarcinoma( Huang et al, 2011 ; Zhang et al, 2013 ; Xiang et al, 2020 ). In addition, down-regulated CLDN10 is correlated with poor prognosis of ovarian cancer and clear cell renal cell carcinoma( Li, Xuan, et al, 2020 ; Yang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…CLDN10, a glandular epithelial marker in epithelial ovarian cancer ( Seo et al, 2010 ), was reported to be a key immune-related gene in clear cell renal cell carcinoma ( Yang et al, 2021 ) and papillary thyroid carcinoma ( Xiang et al, 2020 ). Furthermore, CLDN10 expression has proved to be a prognostic marker for ovarian cancer ( Li Z. et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%